Diet, physiological work and accident incidence of forge workers. - Brooke, J. D.; Toogood, S.; Green, L. F. (Scandinavian Journal of Work, Environment & Health, 1980)
Three experiments were made to study the following three factors in forge workers in a hot shop: (a) the metabolic load of daily work, (b) dietary intake, and (c) the effect of supplementing morning dietary intake with glucose syrup ingestion upon accident incidence. High energy output, mean 9.7 MJ (2,300 kcal), complemented high energy intake, mean 15 MJ (3,600 kcal), a shortage of intake in the morning being compensated for after work in the evening. Alcohol intake represented 1 to 2 MJ (240 to 480 kcal) of the evening intake. Glucose syrup ingestion to reverse increased use of fats in the metabolic fuel in the early morning, in a double-blind design, resulted in a significant reduction of accidents. The effect may lie in altered levels of 5-hydroxytryptamine in the central nervous system. Caution in interpreting the effect upon accidents is necessary since the number of subjects was small (57) and the time span limited (18 weeks).
Keywords: 5-hydroxytryptamine; accident; accident incidence; diet; energy expenditure; forge worker; glucose supplement; physiological work; worker